INDONESIA FACING THE THREAT OF CYBER WARFARE: A STRATEGY ANALYSIS - Ahmad Candra; Suhardi Suhardi; Pratama Dahlian Persadha (Jurnal Pertahanan: Media Informasi ttg Kajian & Strategi Pertahanan yang Mengedepankan Identity, Nasionalism & Integrity, 2021)
The threat of cyber warfare may disturb Indonesia's national interests. For this reason, efforts to create cyber defense forces are essential in dealing with the threat of cyberwar in this technological age. An effective strategy is needed to be carried out by the Government of Indonesia. This article analyzes the strategies implemented by the Government of Indonesia in dealing with the threat of cyber warfare. This study represents the use qualitative approach with an analytical descriptive design. The results of this study explain that the threat of cyber warfare in the future may have an impact that could shake the stability of national security. Through the National Cyber and Crypto Agency (Badan Siber dan Sandi Negara, BSSN) as the leading sector in handling national cyber problems, the Indonesian Government has taken strategic steps to safeguard the national interests and goals of the Indonesian nation and other state institutions stakeholders involved in the management of cyber security and defense. However, in practice, there are still several obstacles such as the unreadiness of regulation, quality, and quantity of human resources and technology infrastructure owned by Indonesia in dealing with any threats that can occur at any time.